Dispute management in Islamic financial services and products: A maqāṣid-based analysis - Oseni, Umar A. (Intellectual discourse, 2015)
The increasing expansion of the Islamic financial services industry beyond its original frontiers has not only come with success stories but has also been affected by the growing preference for litigation as the mode of dispute resolution. Exorbitant legal fees and cost of sustaining protracted litigation are two major challenges that require the attention of major stakeholders in the industry. This paper examines these challenges through a Maqāṣid al-Sharī‘ah focused prism considering the importance of the sustainable dispute management framework in Islamic financial services and products. While singling out the important higher objective (maqṣad) of ḥifẓ al-māl, this study argues that preservation of wealth and financial resources requires effective means of resolving increasingly diverse disputes in the Islamic financial services industry. It is further argued that an effective dispute management framework will consider the original value proposition of Islamic financial intermediation which promotes maṣlaḥah (benefits) and prevents mafsadah (hardship) and ḍarar (financial harm). This makes a case for the affirmative relevance, potential adoption, and systemic modernisation of Islamic dispute management mechanisms such as ṣulḥ, taḥkīm, and muḥtasib in order to fulfil the overarching objective of protection and preservation of wealth and financial resources as one of the core objectives of Sharī‘ah.